Hubungan Antara Pengetahuan Lingkungan, Sikap Peduli Lingkungan, dengan Partisipasi Pengelolaan Lingkungan Sekolah Peserta Didik - Amiruddin, Ilhamsyah; Daud, Firdaus; Rachmawaty, Rachmawaty (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine how environmental knowledge, environmental care attitudes, and school environmental management participation of students and the relationship between each variable. This research is an ex post facto research which is correlational. The population of this study were all students from 3 schools located in Tamalanrea sub-district, namely SMP Negeri 11 Makassar, SMP Negeri 12 Makassar, SMP Negeri 30 Makassar. The research sample used was 349 students who were determined by simple random sampling technique. The research data were analyzed using descriptive statistics and inferential statistics. The results showed that (1) environmental knowledge was in the high category, environmental care attitudes were in the positive category, and school environmental management participation was in the active category; (2) there was a positive and significant relationship between environmental knowledge, environmental care attitudes, and school environmental management participation of students in public junior high schools in Tamalanrea sub-district.